Tabu e reescrita na tradução italiana de A casa dos budas ditosos - Manzato, Elena (2018)
The most recent translation studies propose a descriptive rather than a prescriptive approach, and it is from this perspective that the present study will be set up. This study presents a case study examining in a descriptive way the rewriting of the novel A casa dos budas ditosos by João Ubaldo Ribeiro and how it fits into the Italian cultural system. Through the polysystem studies of Itamar Even-Zohar and through André Lefevere's rewriting theory the Italian and Brazilian cultural contexts are analysed in order to identify the position of the novel within the system, the paratextual elements and the reviews to find out why the translation of the novel was published, and finally the textual elements, that is, various segments of the source text and the target text, to discover the possible rules that determined the translator's behaviour during the translation process. The aim of this research is to understand how cultural issues have been dealt with, those related to the imaginary and above all how the translation of taboos has been managed.